Menolak Stigmatisasi (Upaya Deradikalisasi di Pondok Pesantren Modern Islam [PPMI] Assalaam Surakarta, Indonesia) - Ismail Fahmi Arrauf Nasution; Syafieh Syafieh (TSAQAFAH, 2021)
Lately, pesantren are faced with negative stigmas that are associated as the central understanding of fundamental Islam and become the root for the emergence of radical movements in the name of Islam. This radicalism movement is considered less in line with the moderate Islamic ideology of the archipelago. So that the existence of the pesantren seems to be "the accused". This article aims to show that pesantren as the center of the radicalism movement is not entirely correct. Through participatory observation, in-depth interviews with the caregivers of the Assalaam Modern Islamic Boarding School (PPMI) and literature study. This paper ultimately shows that the Assalaam Modern Islamic Boarding School is one of the pesantren with a democratic pattern of parenting in the teaching aspect, strict (authoritarian) on the reward aspect, and uses a persuasive approach in the persuasion process. Until now, the phenomenon of religious radicalism in the Islamic Modern Islamic Boarding School in Assalaam has not been found, because the implementation of democratic parenting is still effective. Also, the teaching of monotheism and morals which is accompanied by strict supervision among the santri actually acts as a "vaccine" for religious radicalism itself. Especially with the busy pattern of the students in various activities, both intra and extra-curricular, the space for the spread of radicalism is increasingly narrowing.